PENGOLAHAN LIMBAH CAIR INDUSTRI MINUMAN - Indriyati Indriyati (Jurnal Teknologi Lingkungan, 2008)
The organic concentration of soft drink factory waste water has not high organic concentration, therefore one of the alternatives of the treatment technology is using aerobic system : activated sludge. On this observation can be seen that the system can be used as waste water treatment for soft drink that is not so high in COD contain and the criteria parameters design can be fulfilled by process parameters during operation the system. The parameters that are not fulfill the design parameters is caused by the shock loading of toxic material or by the high loading rate of substrate of waste water. Based on parameter criteria as mention above, the efficiency that can be reached of this process is about 61,22%.